Outcomes of Arthroscopic Nerve Release in Patients Treated for Large or Massive Rotator Cuff Tears and Associated Suprascapular Neuropathy: A Prospective, Randomized, Double-Blinded Clinical Trial. Issue 9 (July 2021) - Sachinis, Nikolaos Platon; Papagiannopoulos, Sotirios; Sarris, Ioannis; Papadopoulos, Pericles
Background: Suprascapular neuropathy has been observed in the setting of rotator cuff tears (RCTs), but its association with these tears and their treatment are unclear. Hypothesis: Arthroscopic suprascapular nerve release during rotator cuff repair will not alter the outcomes of neuropathy. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 42 patients with large/massive reparable RCTs and suprascapular neuropathy were recruited and followed up at 6 and 12 months. Electrophysiological results as well as Disabilities of the Arm, Shoulder and Hand (DASH), American Shoulder and Elbow Surgeons (ASES), and Constant scores were evaluated at selected time periods. Patients were randomly assigned to 2 groups. Patients in the control group underwent arthroscopic repair of the rotator cuff without combined arthroscopic release of the superior transverse scapular ligament; in the second group, the superior transverse ligament was released. The primary outcome was to examine full suprascapular nerve recovery through electrophysiological changes between groups. The secondary/tertiary outcomes were analysis of clinical outcomes and assessment of the relation between RCT size and the degree of suprascapular nerve recovery. Patients, clinical staff members, and the neurologist were blinded to the type of surgical procedure. Results: Of 42 patients, 37 completed the follow-up at 12 months (median age, 64 years [range, 50-75 years]). Overall, 17 of 19 (89.5%) patients in the control group and 15 of 18 (83.3%) patients in the nerve release group had full nerve recovery, with no significant difference between the 2 groups. Clinically, all patients in both groups showed a significant improvement ( P < .001), but no significant difference was observed between the 2 groups in terms of 12-month postoperative scores (control group: DASH: median, 5 [range, 0-21]; ASES: median, 88 [range, 83-98]; Constant: median, 86 [range, 70-98]) (nerve release group: DASH: median, 6 [range, 0-25]; ASES: median, 90 [range, 83-98]; Constant: median, 88 [range, 75-98]). Also, no significant difference was found between the 2 groups regarding other secondary and tertiary outcomes. Conclusion: Combined arthroscopic release of the superior transverse scapular ligament and rotator cuff repair in patients with large/massive RCTs and suprascapular neuropathy did not produce statistically significant improved outcomes compared with repair of the rotator cuff alone. Registration: NCT02318381 (ClinicalTrials.gov identifier).